The Influence of Learning Video Media on Students' Interest and Critical Thinking Ability in Junior High School - Musnar Indra Daulay; Dahraini Hannum Daulay (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This research aims to determine how video learning media affects students' interest and critical thinking abilities in class VIII Social Sciences learning at SMPN 2 Bantan. This research uses a quantitative approach with a Nonequivalent Control Group Design, involving two classes: an experimental class using learning videos and a control class using image media. The research instruments are a questionnaire about interest in learning and critical thinking tests via a pretest and a posttest. The population in this study refers to all research subjects, namely 60 eighth-grade students of SMPN 2 Bantan. The sampling technique used was total sampling. This means that all populations were sampled. Primary data were obtained through direct observation of students during the learning process using video learning media and questionnaires that focused on learning interests. Secondary data will be obtained through literature, previous research, or other information sources relevant to the use of video learning media in social studies learning, learning interests, and critical thinking skills. The data analysis technique in this study includes several important steps to dig up relevant information and support research findings. The results showed a significant increase in students' interest in learning and critical thinking abilities in the experimental class compared to the control class. The average learning interest of experimental class students increased from 64.45 to 79.87, and critical thinking ability rose from 62.83 to 75.03. Meanwhile, the increase in the control class was not as substantial as the experimental class. These findings indicate that learning video media effectively increases student engagement and encourages the development of critical thinking skills. Video media can be a strategic alternative for more interactive and meaningful learning.